Li+/Al3+ Composite Solid Electrolyte Based Electro‐Thermal Dual Responsive Devices with Optimized Optical Contrast and Cycle Durability. Issue 11 (25th March 2022) - Jia, Hanxiang; Ji, Xiaowei; Shao, Zewei; Li, Zhongshao; Huang, Aibin; Wen, Zhaoyin; Gu, Sui; Jin, Ping; Cao, Xun
Abstract: The limited optical contrast and band adjustment range are the main factors that restrict chromic materials. In this study, Li + /Al 3+ composite solid electrolyte is incorporated between VO2 and WO3 chromic functional layers to construct a new type of VO2 based electrothermal dual responsive devices. The dual responsive devices deliver optical contrast over 50% and independent modulation of visible and near infrared band. In addition to displaying four reversible optical states in response to environmental temperature and external voltage, the devices effectively utilize the synergistic effect of Li + /Al 3+ hybrid ions. Furthermore, the optimized Li + /Al 3+ composite electrolyte is proved to effectively control phase transition of VO2 and significantly improve the electrochromic properties of WO3 as well. Finally, the electro‐thermal dual responsive devices show excellent service stability in simulated outdoor environment of over 10 000 cycles. Combined with the above advantages, it is expected to develop smart windows and derivative products with large size, long life, remarkable energy saving effect and pleasant comfort. Abstract : A novel structure of electro‐thermal dual responsive devices is constructed with Li + /Al 3+ composite solid electrolyte sandwiched between WO3 and VO2 layer, which can realize dual‐band selective modulation with four reversible functional modes. Moreover, the synergistic effect of Li + −Al 3+ solid electrolyte contributes to excellent optical contrast (over 50%) and superfine service stability over 10 000 cycles.